Acesso à justiça: como os balcões de justiça e cidadania contribuem para garantir o acesso à ordem jurídica justa - Oliveira, Patricia Cerqueira de (2012)
This work is about, in general, the access to Justice, from the perspective of access to the fair legal system, to understand both the access to legal advice and access to the judicial system, from the theoretical view and empirical observation of Justice Branch and Citizenship (BJC), installed by the Court of the State of Bahia in Salvador. The proposal is to undertake a thorough analysis of the BJC to see how they collaborate for the inclusion in the justice system of the population such information on their rights and / or resolve their conflicts. For this, I developed a hypothesis: that the branches of Justice and Citizenship help to give access to the population that seeking guidance about their rights, or has a conflict whose solution has not been formalized legally yet. Then, I set some parameters to conducting the investigation: a) nature of the demand for legal services - the number of calls from BJC Salvador, since those calls that referred to legal advice to those who were related to conflicts of interest; b) number of arrangements in Salvador BJC; c) nature of the conflict led to BJC; d) characteristics of the sites that are situated BJC; e) profile of the services of BJC; f) user’s satisfaction of services provided in the BJC of Salvador. The goal is to summarize some insights come from the research developed in the BJC in city of Salvador, by believing that you may have some use for the development of practice and to think an effective public policy of access to Justice, tailored in the contours of the city of Salvador.